KINETICS AND CRACK GROWTH MECHANISM IN STEEL WITH FERRITE-MARTENSITIC COMPOSITE STRUCTURE - Victor N. Pustovoit; Sergey A. Grishin; Maria V. Zaitseva (Advanced Engineering Research, 2011)
Research results of the crack behavior examination in steels with the ferrite martensitic composite structure are presented. It is shown that the crack propagation rate in these steels is considerably lower than in the same steels with secondary sorbite structure. It is discussed from the perspective of a special mechanism of front crack moving in the composite with tough fibres and plastic matrix.